2019
DOI: 10.1002/brb3.1215
|View full text |Cite
|
Sign up to set email alerts
|

CGRP monoclonal antibody for preventive treatment of chronic migraine: An update of meta‐analysis

Abstract: Background CGRP monoclonal antibody (mAb) is a promising preventive treatment for episodic migraine and has been approved by US FDA recently. But the treatments for chronic migraine are rare. Therefore, we performed meta‐analysis to assess the efficacy and safety of CGRP mAbs in preventing chronic migraine. Methods Database including Cochrane Library and PubMed were systematically searched for randomized controlled trials (RCTs) which are about CGRP mAb in preventing tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 18 publications
6
35
0
1
Order By: Relevance
“…In addition to MSMDs, we performed a subgroup analysis of the above outcomes, which showed that CGRP mAbs showed signi cant e cacy in both episode migraines and chronic migraines, and the results were reliable and stable. The results were similar to those of previous meta-analyses, which included only episodic migraines or chronic migraines [14,[35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…In addition to MSMDs, we performed a subgroup analysis of the above outcomes, which showed that CGRP mAbs showed signi cant e cacy in both episode migraines and chronic migraines, and the results were reliable and stable. The results were similar to those of previous meta-analyses, which included only episodic migraines or chronic migraines [14,[35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…All the trials indicated better outcomes and prevention of migraine with anti-CGRP medication, but the efficacy seemed to be diversified by the different interval and period of drug administration [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64]. Though the synthesized evidences consistently confirmed that anti-CGRP had no serious adverse events reported and the effects of anti-CGRP remain controversial due to differences in follow-up and the percentage of response rate [65,66,67,68,69]. Some previous meta-analyses and systematic reviews analyzed a small amount of the trials [67,68], and one article containing a larger amount of trials showed results with large heterogeneity by estimated analysis due to the variety of features and units of different trials [65].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a series of CGRP antagonists and monoclonal antibodies against the CGRP system demonstrated therapeutic benefits in several controlled clinical trials conducted on large populations [43,69]. However, the widespread expression of CGRP and its receptors throughout the human body [70] could lead to unwanted side effects, including a cardiovascular risk [71][72][73].…”
Section: Discussionmentioning
confidence: 99%